Mortality and associated risk factors between young and elderly maintenance haemodialysis patients: a multicentre retrospective cohort study in China. Issue 2 (6th February 2023) - Chen, Jilin; Wang, Jinling; Liu, Ying; Zhao, Guangben; Gao, Fengdi; Hu, Menghong; Wang, Weidong; Lin, Hong-li
Abstract : Objectives: Mortality and associated risk factors in young and elderly haemodialysis patients with end-stage kidney disease (ESKD) have not been well examined in China. Therefore, we aimed to assess the all-cause mortality and risk factors associated with all-cause mortality between young and elderly haemodialysis patients in China. Design: A population-based multicentre retrospective cohort study. Setting: Using the Dialysis Initiation based on Fuzzy mathematics Equation study data, patients with ESKD undergoing maintenance haemodialysis from 24 centres in China from 1 January 2008 to 30 September 2015. Participants: 1601 enrolled patients with ESKD were categorised into young group (18–44 years old) and elderly (≥60 years old) group. Outcome measures: The primary outcome was all-cause mortality. We estimated overall survival using a log-rank test. Cox proportional hazard regression analysis was implemented to identify risk factors and HR associated all-cause mortality. Results: During a mean follow-up of 48.17±25.59 months, of the 1601 subjects, 319 (19.92%) patients death, including 64 (9.97%) in young group and 255 (26.59%) in elderly group, respectively. The cumulative survival in elderly group was lower than young group (Log Rank tests=63.31, p<0.001). Multivariate Cox proportional hazards analysis showed the cardiovascular disease (HR, 2.393; 95% CI 1.532 to 3.735; p<0.001), cerebrovascular disease (HR, 2.542; 95% CI 1.364 to 4.739; p=0.003) and serum albumin<3.5 g/dL (HR, 1.725; 95% CI 1.091 to 2.726; p=0.020) at the haemodialysis initiation were associated with increased risk of all-cause mortality in elderly groups; however, the cardiovascular disease only was associated with increased risk of all-cause mortality in young groups. Conclusions: The all-cause mortality of elderly haemodialysis patients were higher than young haemodialysis patients in China. Identified risk factors associated all-cause mortality may inform development of age-appropriate treatment, intervention strategies and improve survival prognosis of this unique population.